Influence of Liquidity, Leverage, Profitability and Company Size to Company Value (Empire Study on Food Sub-Sector Companies and Beverages Listed on The Indonesia Stock Exchange Period 2014-2017) - Sabaruddin Zen; Qiqy Elizhia Pujarani (Universitas Negeri Semarang, 2023)
The research aims to analyze the influence of liquidity, leverage, profitability and firm size on the firm value of food and beverage sub-sector company listed on the Indonesia Stock Exchange period 2014-2017. Variables that used tomeasure variable liquidity are current ratio (CR), variable leverage measured by debt to equity ratio (DER), variable profitability measured by return on equity (ROE), and firm size according to the total assets and firm value measure by (the ratio PBV). Sample of this research are food and beverage manufacturing company listed on the Indonesia Stock Exchange period 2014-2017 with the total 18 companies. By using the purposive sampling, it took 13 companies as the sample of research. Analysis technique used are descriptive analysis, test the assumption classical which includes normality test, multi-co linearity test, heteroscedasticity test and autocorrelation test, with a significance alpha 5 percent and 1 percent. Panel analysis data which multiple regression linear analysis and the hypothesis test includes f statistic test, t test statistic and determination test. The research result shows that the liquidity variable (CR) does not influence the firm value. Leverage variable (DER) has the positive influence and significantly to firm value (PBV). Profitability has the positive infuence and significantly to firm value (PBV) meanwhile the firm size variable (Ln Total Asset) has the negative influence and significantly to firm value (PBV).